Peran Branding Dan Word of Mouth dalam Meningkatkan Costumer Engagement pada UMKM Kuliner di Car Free Day Medan (Studi Kasus : Tiramisu Sodok) - Shafa Azalia Putri; Shafwatul Hilwa; Suci Aldha Eviolla; T. Rahmah Rindiyani; Zainarti (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Car Free Day (CFD), a weekly event held every Sunday, functions not only as a public space for healthy activities such as walking and exercising, but has also transformed into a significant center of business opportunities, particularly for Micro, Small, and Medium Enterprises (MSMEs). The high concentration of visitors makes the CFD area a potential market with a large number of consumers. This study focuses on a case study of “Tiramisu Sodok,” a sweet culinary business that is popular, especially among young people, which utilizes CFD as its selling location. The main objective of this research is to analyze the role of Word of Mouth (WOM) as an effective marketing strategy in increasing the number of customers and business profitability. The research method used is a combination of literature studies from articles and journals related to economics and business, as well as direct interviews with the business owner. The results indicate that word-of-mouth recommendations significantly serve as a major opportunity in increasing brand visibility, expanding the customer base, and ultimately improving the profitability of MSMEs operating in CFD areas.